Genetics of wood characters of black spruce (Picea mariana (Mill.) B.S.P.) in Newfoundland, Canada - Khalil, M.A.K. (JD Sauerlaender's Verlag, 1985)
The variation and relative control of genotype and envi ronment over 11 wood characters in black spruce (Picea mariana (MILL.) B.S.P.) were studied to identify populations with superior pulping qualities. A four- and three-level cluster sampling scheme was adopted and the statistical and genetic analyses comprised analyses of variance, BoN FERRONI t-tests, repeatability calculations and multiple re gressions. Trees, discs and populations rank from highest to lowest as sources of variation in most characters. Within trees, the trend varies with character. There are weak north-south trends in relative densities, alcohol-benzene and sodium hydroxide solubilities and fibre length and wall thickness. Regression analyses of the ,squares of longitude and altitude show a negative and a positive influence respectively on sodium hydroxide solubility. Temperature and precipitation appear most frequently in different combinations in other regression equations. Repeatability values are good estimates of heritabilities. All characters except fibre wall thickness have high heritability (R ): 0.30). The environ mental factors studied have a significant influence on the non-genotypic portion of variation in all characters except fibre and lumen diameters (tangential section) and alcohol benzene .solubility. Populations 11, 16 and 19-23 have superior pulping qualities.